2009
DOI: 10.1021/bm900203w
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functionalization of Titanium with Carboxymethyl Chitosan and Immobilized Bone Morphogenetic Protein-2 for Enhanced Osseointegration

Abstract: Orthopedic implant failure has been attributed mainly to loosening of the implant from host bone, which may be due to poor bonding of the implant material to bone tissue, as well as to bacterial infection. One promising strategy to enhance tissue integration is to develop a selective biointeractive surface that simultaneously enhances bone cell function while decreasing bacterial adhesion. In this in vitro study, the surfaces of titanium alloy substrates were functionalized by first covalently grafting carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(99 citation statements)
references
References 75 publications
6
93
0
Order By: Relevance
“…XPS showed heparin was successfully grafted on anodized Ti surfaces, as indicated by higher C and N peaks. In a previous study, successful immobilization of rhBMP-2 on surface of carboxymethyl chitosan (CMCS)-grafted Ti was attributed to the covalent bonds formation between the carboxyl groups of CMCS and the amine groups of rhBMP-2 [53]. In the present study, successful anchoring of rhBMP-2 and rhPDGF-BB to Hepa/Ti surfaces was demonstrated by further increases in N content.…”
Section: Discussionsupporting
confidence: 61%
“…XPS showed heparin was successfully grafted on anodized Ti surfaces, as indicated by higher C and N peaks. In a previous study, successful immobilization of rhBMP-2 on surface of carboxymethyl chitosan (CMCS)-grafted Ti was attributed to the covalent bonds formation between the carboxyl groups of CMCS and the amine groups of rhBMP-2 [53]. In the present study, successful anchoring of rhBMP-2 and rhPDGF-BB to Hepa/Ti surfaces was demonstrated by further increases in N content.…”
Section: Discussionsupporting
confidence: 61%
“…Some polymeric surfaces consist of hydrophilic, highly hydrated, non-charged surfaces to reduce any surface interactions. Dextran and polyethylene glycol (PEG) surfaces have been shown to be effective in suppressing protein adhesion, platelet adhesion, bacterial adhesion and biofilm formation of oral relevant pathogens, such as S. aureus, S. sanguinis, L. salivarius S. mutans and S.gordonii 29,96,[101][102][103]107) . Lignin, a complex, amorphous organic polymer found in plant tissues, exhibits antibacterial activity against S. aureus, P. aeruginosa and C. famata 51) .…”
Section: Polymeric Coatingsmentioning
confidence: 99%
“…For instance, PEG surfaces hinder not only non-specific protein adsorption and bacterial attachment but, to the same degree, the adhesion of mammalian cells. Recent studies have attempted to promote specific binding interactions between host tissues and implant materials by immobilizing bioactive proteins, such as cell adhesive proteins containing arginine-glycine-aspartic acid (RGD) sequences or bone morphogenetic proteins 28,29,98,99,112,163) . Peptide-functionalized polymers exhibit a selective biointeraction pattern that may be useful in dental implantology, as they can enhance attachment of fibroblasts and osteoblasts while reducing non-specific protein adsorption, thus resulting in reduced bacterial adherence.…”
Section: Polymeric Coatingsmentioning
confidence: 99%
“…The medium was changed twice per week. Alkaline phosphatase activity (ALP) was determined after 1 and 2 weeks as previously described (31). Briefly, the cell layers were first washed with PBS.…”
Section: Differentiation Of Hmscsmentioning
confidence: 99%